Implementasi Konsep Addiction in Catchiness pada Perancangan Interior “Rumah Cokelat” di Surabaya - Jeanny Florencia Halim (Intra, 2016)
Chocolate is one of the most special cocoa products compared to other products. Chocolate contains flavanol compounds that function to soothe the nerves. This chocolate’s compound is what people need, especially in Surabaya. Most people in Surabaya are experiencing stress, discomfort, and other problems due to the activities and conditions of congested city. So that chocolate has the potential to be appreciated as a place where people can be recreation, relaxation, get information and share their creativity by utilizing chocolate as the basic idea of making the place’s design. Interior Design